2014
DOI: 10.2337/dc14-1196
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Structural Brain Changes in Type 2 Diabetic Patients and Their Longitudinal Progression With Intensive Control of Blood Glucose

Abstract: OBJECTIVEUnderstanding the effect of diabetes as well as of alternative treatment strategies on cerebral structure is critical for the development of targeted interventions against accelerated neurodegeneration in type 2 diabetes. We investigated whether diabetes characteristics were associated with spatially specific patterns of brain changes and whether those patterns were affected by intensive versus standard glycemic treatment.RESEARCH DESIGN AND METHODSUsing baseline MRIs of 488 participants with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…In T2D individuals, treatment with metformin has been reported to reduce the risk of cognitive decline over time [32]. Neuroimaging studies report corresponding findings suggesting a link between chronic hyperglycemia and brain atrophy [33], reduced brain volume [34], and cognitive function [35] in T2 diabetic subjects.…”
Section: Discussionmentioning
confidence: 95%
“…In T2D individuals, treatment with metformin has been reported to reduce the risk of cognitive decline over time [32]. Neuroimaging studies report corresponding findings suggesting a link between chronic hyperglycemia and brain atrophy [33], reduced brain volume [34], and cognitive function [35] in T2 diabetic subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Cross-sectional data from over 3000 patients with T2DM demonstrated an age-adjusted inverse relationship between cognitive function and A1C levels [32]. However, prospectively collected data found that total brain volumes were higher in the intensive treatment group but cognitive outcomes were not significantly different between the two groups [33, 34]. …”
Section: Clinical Effects Of Diabetes On Cognitionmentioning
confidence: 99%
“…There is evidence of MRI abnormalities including a reduction in hippocampal volumes in both animal models [37•] and human subjects [33, 34, 3840] with IGR. With improvement in glycemic control, there is stabilization of the rate of brain atrophy [33, 34].…”
Section: Mri Diagnosis Of Structural and Functional Changes In The DImentioning
confidence: 99%
See 2 more Smart Citations